On one problem for comonotone approximation - Nesterenko, A. N.; Petrova, T. O. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
For a comonotone approximation, we prove that an analog of the second Jackson inequality with generalized Ditzian - Totik modulus of smoothness ω^φ_k, r is invalid for (k, r) = (2, 2) even if the constant depends on a function.